2016
DOI: 10.3390/info7030047
|View full text |Cite
|
Sign up to set email alerts
|

An mHealth Tool Suite for Mobility Assessment

Abstract: Abstract:The assessment of mobility and functional impairments in the elderly is important for early detection and prevention of fall conditions. Falls create serious threats to health by causing disabling fractures that reduce independence in the elderly. Moreover, they exert heavy economic burdens on society due to high treatment costs. Modern smartphones enable the development of innovative mobile health (mHealth) applications by integrating a growing number of inertial and environmental sensors along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The SOMS was designed to deliver overuse prevention, diagnosis, and treatment services that are based on scientific evidence, which was mostly collected by the developed SOMS smartphone background software application (“app”). The idea was to use the concept of mobile technology that has been extensively applied and widely successful in other healthcare systems (711) to aid self-control and support behavioral change in such a way that overuse is controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The SOMS was designed to deliver overuse prevention, diagnosis, and treatment services that are based on scientific evidence, which was mostly collected by the developed SOMS smartphone background software application (“app”). The idea was to use the concept of mobile technology that has been extensively applied and widely successful in other healthcare systems (711) to aid self-control and support behavioral change in such a way that overuse is controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, new measurements technologies (portable, inexpensive, with network connectivity, and also for complex body movement [8]) are applied to the field of game and augmented reality [9]. These new devices in the context of augmented reality suggest that these tools can be used to prevent falls in the elderly population thanks to the regular monitoring of fall risk [10][11][12][13]. Physical exercise protocols carried out by using video games combining exercise, known as exergames [14,15], generate a lot of interest in the field of fall prevention especially when it is based on low-cost devices such as Nintendo Wii, Microsoft Kinect, or Asus Xtion.…”
Section: Related Workmentioning
confidence: 99%
“…Efforts to develop mobile health applications that integrate with smartphones is an effort made to detect mobility problems faced by the elderly in the community can be immediately known. Madhushri, Dzhagaryan, Jovanov, & Milenkovic, (2016), indicated that the application of the detection instrument of mobility problems in older adults using mobile applications integrated into a smartphone could shorten the analysis time and helps in monitoring continuously and can assess the effectiveness of exercise or therapy program being undertaken by the elderly. Based on the results of studies conducted by Blackman, Zoellner, Berrey, et al, (2013) shows that the effectiveness of data reporting using M-Health application reaches 53.3% to 60% with reliability level above 90%.…”
Section: Resultsmentioning
confidence: 99%